The complex nature of lncRNA-mediated chromatin dynamics in multiple myeloma - Nylund, Patrick; Garrido-Zabala, Berta; Kalushkova, Antonia; Wiklund, Helena Jernberg (Frontiers in Oncology, 2023)
Extensive genome-wide sequencing efforts have unveiled the intricate regulatory potential of long nonprotein coding RNAs (lncRNAs) within the domain of haematological malignancies. Notably, lncRNAs have been found to directly modulate chromatin architecture, thereby impacting gene expression and disease progression by interacting with DNA, RNA, and proteins in a tissue-or condition-specific manner. Furthermore, recent studies have highlighted the intricate epigenetic control of lncRNAs in cancer. Consequently, this provides a rationale to explore the possibility of therapeutically targeting lncRNAs themselves or the epigenetic mechanisms that govern their activity. Within the scope of this review, we will assess the current state of knowledge regarding the epigenetic regulation of lncRNAs and how, in turn, lncRNAs contribute to chromatin remodelling in the context of multiple myeloma.